2012
DOI: 10.1007/s12307-012-0118-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers in Peripheral Blood of Iranian Women with Breast Cancer

Abstract: A biomarker is a quantifiable laboratory measure of a disease specific biologically relevant molecule that can act as an indicator of a current or future disease state. The purpose of this study is to detect the expression of RNA biomarkers using Cytokeratin 19 (CK-19), Mammaglobin (MAM), Carcinoembryonic antigen (CEA), Mucin (MUC), C-Myc, erb-B2, a proliferation marker (Ki-67), Epidermal growth factor receptor (Her2/neu) and Estrogen receptor (ER) in Iranian women who were diagnosed with breast cancer. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In several studies, CK19 as a marker for epithelial cells has been used in the diagnosis of CTC in peripheral blood of patients with breast cancer. 5 , 14 , 15 CK19 expression often changed in epithelial cancer, and especially, it has been widely used as a marker for the diagnosis of breast epithelial cells. 16 , 17 CK19 mRNA indicates the presence of CTCs in some cancers, especially breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, CK19 as a marker for epithelial cells has been used in the diagnosis of CTC in peripheral blood of patients with breast cancer. 5 , 14 , 15 CK19 expression often changed in epithelial cancer, and especially, it has been widely used as a marker for the diagnosis of breast epithelial cells. 16 , 17 CK19 mRNA indicates the presence of CTCs in some cancers, especially breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It can be an appropriate diagnostic marker for detection of tumor cells in the peripheral blood of patients with cancer. 5 , 6 In several studies, CK19 was used as a marker for the detection of cancer cells in the bone marrow, peripheral blood, and lymph nodes. 6 8 In addition, CK19 marker is considered as an independent prognostic indicator in patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…erb-B2 molecular marker in peripheral blood was shown with low sensitivity (44%) and good specificity (90%), with only 12% false positive results in healthy controls, in our study. In our previous study, we found detected transcripts of erb-B2 in peripheral blood of 60 pretreated BC patients that was significantly different from 30 healthy controls (p<0.05) (Oloomi et al, 2013). In other study, plasma erb-B2 mRNA was shown in both peripheral blood of BC patients (43.3%) and healthy females (10%) (Xu et al, 2006).…”
Section: Discussionmentioning
confidence: 80%
“…F o r e r b -B 2 c D N A F o r w a r d p r i m e r 5'-CTGGTGACACAGCTTATGCCCT-3' and Reverse primer 5'-ATCCCCTTGGCAATCTGCA-3' were used. Specific primers were used for erb-B2 in our study (Oloomi et al, 2013). The RT-PCR product for GAPDH and erb-B2 was 319 and 113 base pair (bp), respectively.…”
Section: Reverse Transcriptase -Polymerase Chain Reactions (Rt-pcr)mentioning
confidence: 99%
“…Gene-expression profiling has altered previous perceptions about BC and could be considered as a new molecular diagnosis tool [ 9 , 10 ]. Moreover, a defined molecular marker coexpression panel for each patient with BC based on pathological characteristics and modulation assessment of expression level after treatment can provide personalized treatment for patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%